2016
DOI: 10.1016/j.seizure.2016.05.001
|View full text |Cite|
|
Sign up to set email alerts
|

Quality of life in epilepsy in Bhutan

Abstract: There are potentially modifiable associations with low QOLIE. Addressing the educational level and self-perceived stigma of PWE may have an especial impact. The low QOLIE in Bhutan may reflect cultural approaches to epilepsy, health services, or other factors including those outside of the health sector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 33 publications
(37 reference statements)
3
18
5
Order By: Relevance
“…Regarding quality of life level in the studied sample it was noted that the highest quality of life scores were in the medication effects domain with a mean and standard deviation of 74.49 ± 25.46 while the lowest quality of life scores were in the emotional well-being domain with a mean and standard deviation of 53.40 ± 17.75. This study result disagree with the results documented by Saadi et al [17] who found the highest scores in the overall QOL with a mean and SD of (56.8 ± 18.6) and the lowest QOL in the seizure worry with a mean and SD of (32.1 ± 24.0).…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding quality of life level in the studied sample it was noted that the highest quality of life scores were in the medication effects domain with a mean and standard deviation of 74.49 ± 25.46 while the lowest quality of life scores were in the emotional well-being domain with a mean and standard deviation of 53.40 ± 17.75. This study result disagree with the results documented by Saadi et al [17] who found the highest scores in the overall QOL with a mean and SD of (56.8 ± 18.6) and the lowest QOL in the seizure worry with a mean and SD of (32.1 ± 24.0).…”
Section: Discussioncontrasting
confidence: 99%
“…This result is in agreement with other studies. 29,32,35,40 Epileptic patients with comorbid depression were negatively associated with quality of life. This finding was similar to results from other studies.…”
Section: Dovepressmentioning
confidence: 99%
“…In the current study, we had a mean higher quality of life score in epileptic patients, compared to a study conducted in Kenya (mean score of 49.90), Bhutan (mean score of 48.9), and Poland (mean score of 55.18). [29][30][31] The possible reason for this difference might be sample size difference, clinical characteristics of the participants, sociocultural difference and study setting. The sample size was higher in this study compared to the sample of Kenya, Bhutan, and Poland.…”
mentioning
confidence: 99%
“…Lower educational attainment level was observed to have an independent, negative association with QOLIE (p < 0.05). 17 Subjects with family history of epilepsy have a worse mental component. It was the only statistically significant variable related to QoL (p < 0.021).…”
Section: Resultsmentioning
confidence: 99%